2012
DOI: 10.1002/jemt.22045
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal and liver changes after chronic ketamine and ketamine plus alcohol treatment

Abstract: The effects of long-term chronic ketamine treatment on the intestine and the liver were studied in the ICR mice which had daily intraperitoneal injection of ketamine at 30 mg/kg per day for 7 months. The intestine showed no significant pathology after treatment but had a decrease of the positive sites of proliferative cell nuclear antigen in the mucosae of the intestines after ketamine and ketamine plus alcohol (added in the last month) treatment. No significant apoptosis (via TUNEL) nor necrosis (via lactic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…It is well known that, in addition to changes of liver enzymes, ketamine addiction for long periods of time in adult humans also contributed to other significant damage in the liver, including microscopic damages, decreased storage of glycogen and formation of sites of fibrosis in non-pregnant adults [7]. In this study, we demonstrated a decrease in proliferation ability as reflected by lower numbers of PCNA-positive nuclei per unit area of the livers in the neonates of mice with mothers treated with ketamine during pregnancy, in comparison to a control group with mothers injected with saline only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that, in addition to changes of liver enzymes, ketamine addiction for long periods of time in adult humans also contributed to other significant damage in the liver, including microscopic damages, decreased storage of glycogen and formation of sites of fibrosis in non-pregnant adults [7]. In this study, we demonstrated a decrease in proliferation ability as reflected by lower numbers of PCNA-positive nuclei per unit area of the livers in the neonates of mice with mothers treated with ketamine during pregnancy, in comparison to a control group with mothers injected with saline only.…”
Section: Discussionmentioning
confidence: 99%
“…When combining ketamine treatment with a month of alcohol, the increase of glutamate oxaloacetate transaminase (GOT, also named aspartate aminotransferase, AST) in the liver was significantly more than those of ketamine alone, along with large foci of fibrosis [5]. Loss of glycogen was another principle finding of ketamine induced damage in the liver [7]. Although the toxicity in the livers of adult addicts was rather clear, in this paper we explore whether ketamine produced equivalent changes in the livers of the pregnant abusers as well as in the livers of their offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced glycogen store in hepatocytes is related to an increased susceptibility to hepatotoxicity (Stadler et al, 2005). In mice, chronic ketamine treatment also decreases glycogen in liver, reflecting either a failure of glycogen synthesis or an increase of glycogenolysis (Wong et al, 2012). Other studies also reported that ketamine can promote hepatic bioenergetic deterioration with concomitant reduction of ATP production (Takahashi et al, 1998), gluconeogenesis (Sear and McGivan, 1979) and increased glycogenolysis (Machado et al, 2009) which may be associated with an increase of blood glucose levels (Dawson et al, 2013 andRodrigues et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Being one of the noncompetitive NMDA receptor antagonists like phencyclidine and MK801, it would produce schizophrenia like psychosis in human (Dickerson and Sharp, 2006). Unfortunately, ketamine has now become an abusive drug in many parts of the world and chronic and prolonged usage led to damages of many organs in experimental animals (Yeung et al, 2009; Chan et al, 2011; Tan et al, 2011a; Wai et al, 2012; Wong et al, 2012). The damage on the nervous system included neuronal loss, synaptic changes, changes in functional magnetic resonance imaging (fMRI) activities, and the formation of mutated tau protein in neurons as described in models of rodents and monkeys (Yeung et al, 2010a; Sun et al, 2011; Yu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%